EKSISTENSI LEMBAGA BANTUAN HUKUM (LBH) DALAM MEMBERIKAN LAYANAN HUKUM KEPADA MAYARAKAT DI KABUPATEN GORONTALO - Nirwan Yunus; Lucyana Djafaar (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2008)
The research about the existence legal aid institute in give to public service in Gorontalo regency is normative legal research. Guarantee to protection of human right for every people is absolute required in a state claiming to rule of law. The of legal aid institute is not only functioning assists or holds a brief for weak small people faces a law process especially jurisdiction process, but the legal aid institute to become pioneer and master mind various modernity is including law of recondition. Be hinge give service of legal aid to public lacked, the legal aid institute to have ambition for educate public in the broadest possible meaning with a purpose to grow and constructs awareness of rights as law subject. The result of research in field existence legal aid institute in Gorontalo regency to be proved less play role in law enforcement and rule of law. This thing is provable from various cases happened entangling indigent public unable to get attention compared to cases entangling man is residing. The data in field is found by many cases people indigent, has not entangled legal aid institute and or the advocates.